PERLINDUNGAN HUKUM TERHADAP PEKERJA ANAK DI SEKTOR INFORMAL (Studi Kasus Di Kota Kediri) - Netty Endrawati (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Normatively children forbidden to work. To guarantee the protection of working children has been out various laws, which exist principles prohibit children to work, and when forced to work, then the normative such children should obtain legal protection enough guarantee, and the effort was one of them is done through provisions of Article 69 paragraph (2) Law No. 13 of 2003 concerning Manpower. The implementation of legal safeguards against children working in the practice of having many barriers, including economic factors that would be a driver of why kids should be working, cultural factors, factors community participation, and lack of coordination and cooperation, government aparatur limitations personnel assigned to conduct surveillance, and other factors directly or indirectly, so until now the phenomenon of children working in the informal sector is almost always can be found all over Indonesia, both in big cities and in rural areas. Key words: working children, legal protection, the interests of the child